Isaiah in the New Testament: The New Testament and the Scriptures of Israel. Edited by Steve Moyise and Maaten J. J. Menken - Foster, Paul (The journal of theological studies, 2008)
This is the second in the series of volumes subtitled The New Testament and the Scriptures of Israel. This book focuses on the way that the writings from Isaiah are used primarily in the New Testament, but also in roughly contemporary second Temple Jewish literature. The editors state, in over-exaggerated terms, that ‘the focus is on the book of Isaiah, whose influence is everywhere in the New Testament documents’ (p. 1). They note both the occurrence of quotations and perhaps to a greater degree the presence of ‘a host of allusions, and one could even say that certain central theological concepts, such as “gospel”, derive from Isaiah’ (p. 1).